ANALISIS KELAYAKAN BISNIS DITINJAU DARI ASPEK PRODUKSI DAN ASPEK PEMASARAN PADA UMKM MAHKOTA UTARA - Putri, Dini Lara; Okianna, Okianna; Kuswanti, Heni (Universitas Tanjungpura, 2025)
The research aims to analyze the feasibility of Mahkota Utara MSMEs based on two aspects, namely production aspects and marketing aspects. This research uses a qualitative approach with a case study method. The informants in the study were 6 people with data collection techniques carried out by observation, interviews and documentation techniques. Data analysis techniques use data reduction, data presentation and conclusion drawing, with data validity testing using triangulation of techniques and sources. The results showed that overall the business has a good level of feasibility to be developed in the future. In the production aspect, business location and operational efficiency have supported the sustainability of the business, but technology and raw material management need to be efficient in the future, as an investment in modern technology and improving raw material management strategies. Meanwhile, in the marketing aspect, the business is declared feasible with a market segmentation strategy, target market, market position, product, price, and distribution showing good results. However, promotion strategies need to be optimized in the future. Improving production and marketing efficiency for Mahkota Utara MSMEs in the future has the potential to develop sustainably and be highly competitive in business.